Agile cavity ringdown spectroscopy enabled by moderate optical feedback to a quantum cascade laser - Qinxue Nie; Yibo Peng; Qiheng Chen; Ningwu Liu; Zhen Wang; Cheng Wang; Wei Ren (Opto-Electronic Advances)
Cavity ringdown spectroscopy (CRDS), relying on measuring the decay time of photons inside a high-finesse optical cavity, offers an important analytical tool for chemistry, physics, environmental science, and biology. Through the reflection of a slight amount of phase-coherent light back to the laser source, the resonant optical feedback approach effectively couples the laser beam into the optical cavity and achieves a high signal-to-noise ratio. However, the need for active phase-locking mechanisms complicates the spectroscopic system, limiting its primarily laboratory-based use. Here, we report how passive optical feedback can be implemented in a quantum cascade laser (QCL) based CRDS system to address this issue. Without using any phase-locking loops, we reflect a moderate amount of light (–18.2 dB) to a continuous-wave QCL simply using a fixed flat mirror, narrowing the QCL linewidth from 1.2 MHz to 170 kHz and significantly increasing the laser-cavity coupling efficiency. To validate the method’s feasibility and effectiveness, we measured the absorption line (P(18e), 2207.62 cm−1) of N2O in a Fabry–Perot cavity with a high finesse of ~52000 and an inter-mirror distance of 33 cm. This agile approach paves the way for revolutionizing existing analytical tools by offering compact and high-fidelity mid-infrared CRDS systems.